Not from here : a memoir - Johnson, Allan G. (Temple University Press, 2015)
"When Allan Johnson asked his dying father where he wanted his ashes to be placed, his father replied--without hesitation--that it made no difference to him at all. In his poignant, powerful memoir, Not from Here, Johnson embarks on an extraordinary, 2,000-mile journey across the Upper Midwest and Northern Plains to find the place where his father's ashes belonged. As a white man with Norwegian and English lineage, Johnson explores both America and the question of belonging to a place whose history holds the continuing legacy of the displacement, dispossession, and genocide of Native peoples. More than a personal narrative, Not from Here illuminates the national silence around unresolved questions of accountability, race, and identity politics, and the dilemma of how to take responsibility for 'a past we did not create.' Johnson's story--about the past living in the present; of redemption, fate, family, tribe, and nation; of love and grief--raises profound questions about belonging, identity, and place"--